A lower atherogenic index of plasma was associated with a higher incidence of sarcopenia - Zhiping Duan; Yunda Huang; Xiaoling Liu; Huiyu Tang; Guihua Jiang; Wei Huang; Runfen Du; Dan Zhou; Hong Yang (Scientific Reports)
Abstract Sarcopenia is an age-related muscle senescence disease that leads to functional limitations, physical disability and premature death in older adults. Atherogenic index of plasma (AIP) is a novel indicator of atherosclerotic status based on triglycerides and high-density lipoprotein cholesterol. The aim of this study was to investigate the association between AIP and new-onset sarcopenia and its components among middle-aged and older adults in a Chinese community. This cohort study included 7,992 participants who were free of sarcopenia in 2011 in the China Health and Retirement Longitudinal Study and were followed up in 2013 and 2015. Sarcopenia was assessed using the recommendations of the Asian Working Group for Sarcopenia 2019. Longitudinal associations between AIP and sarcopenia and its components were assessed using Cox proportional risk regression modeling. The results showed that AIP was negatively associated with sarcopenia [HR and 95% CI: 0.73 (0.62–0.86)]; with muscle mass [β and 95%CI: 0.49 (0.4–0.57)], skeletal muscle mass index [β and 95%CI: 0.17 (0.15–0.2)], and grip strength [β and 95% CI: 0.17 (0.15–0.2)] being positively correlated. A lower AIP was associated with a lower muscle mass and handgrip strength and higher incidence of sarcopenia. Regular measurement of AIP in the middle-aged and older population in the community can help in the early diagnosis and intervention of sarcopenia.